PERCEIVING THE EUROPEAN UNION: INFLUENCE OF THE ERASMUS PROGRAM ON STUDENT OPINIONS - Berić, Jovan; Radujko, Dušan (Serbian political thought, 2023)
This paper has the goal of presenting experiences of Faculty of Political Sciences, University of Belgrade students during their Erasmus program stays and to provide insights into the ways in which it influenced their opinions of the European union and the European integration process. After presenting the goals of the Erasmus program and the strategic documents of the Republic of Serbia within the field off education, the paper places the process of forming political opinions in theoretical context. The experiences of students which participated in the program within the 2017-2019. period are analyzed from the perspective of Erasmus program goals and the influence they have on the opinions and social networking of the participants. The paper concludes that all of the participants entered the program with already formed positive opinions on the European integration process, while also noting a development of skills and values related to the concept of European identity, such as openness and tolerance. Furthermore, the research finds that among the program participants there was no sense of otherness developed during their stay and that they were not faced with any serious administrative challenges which could negatively influence their perception of the European union. However, in order to encourage further development of the program, one must keep in mind that there exist certain barriers in the area of communicating information about requirements and procedures during application, as well as during the process of selecting and approving classes.
Keywords: Erasmus program; Student exchange; Student attitudes; European integration; Social networking; Republic of Serbia